Learning Heat and Its Transfer with Power Point Learning Media for Grade V Students of Elementary School - Rozali, Dini; Ramadan, Zaka Hadikusuma (International Journal of Elementary Education, 2021)
Currently, media used as one of the learning components had not been fully used and developed according to the needs. The current characteristics and conditions and the teaching-learning process were fixated only on student textbooks. The purpose of this research was to develop  Powerpoint learning media for learning 3,4 and 5 on theme 6 "Heat and Displacement," Sub-theme 1 "Temperature and Heat," for grade V elementary school students. However, in its implementation, this research is limited to product validation tests conducted at the development stage of the product. The subjects of this study were 6 experts, consisting of 2 material experts, 2 linguists and 2 design experts, and grade V elementary students. The data collection methods are interviews and validation sheets. The analysis was qualitative and quantitative analysis of interview data and validation sheets. The results stated that  PowerPoint learning media was worth looking at in terms of materials, language, and design with an average score of  93.7%, with a very valid category. So,  Powerpoint learning media was worth using.